2018
DOI: 10.1093/infdis/jiy688
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Value of Different Zika Vaccination Strategies to Prevent and Mitigate Zika Outbreaks?

Abstract: Background While the 2015–2016 Zika epidemics prompted accelerated vaccine development, decision makers need to know the potential economic value of vaccination strategies. Methods We developed models of Honduras, Brazil, and Puerto Rico, simulated targeting different populations for Zika vaccination (women of childbearing age, school-aged children, young adults, and everyone) and then introduced various Zika outbreaks. Sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, they do not show the effect in risk groups nor assume herd immunity from previous outbreaks as we did; Durham et al (2018) showed that immunizing females aged 9 to 49 years with a 75% effective vaccine and a coverage of 90%, would reduce the incidence of prenatal infections by at least 94% [41]. Similarly, Bartsch et al (2018) showed that women of childbearing age or young adults would be an ideal target group for vaccination [42]. Valega-Mackenzie et al (2018) formulated a vaccination model for ZIKV transmission that included mosquito and sexual transmission [43].…”
Section: Interpretation In Comparison With Other Studiesmentioning
confidence: 58%
“…However, they do not show the effect in risk groups nor assume herd immunity from previous outbreaks as we did; Durham et al (2018) showed that immunizing females aged 9 to 49 years with a 75% effective vaccine and a coverage of 90%, would reduce the incidence of prenatal infections by at least 94% [41]. Similarly, Bartsch et al (2018) showed that women of childbearing age or young adults would be an ideal target group for vaccination [42]. Valega-Mackenzie et al (2018) formulated a vaccination model for ZIKV transmission that included mosquito and sexual transmission [43].…”
Section: Interpretation In Comparison With Other Studiesmentioning
confidence: 58%
“…In addition, DNA vaccines are relatively easy and cost-effective to manufacture on a large scale. They have excellent safety profiles for women of childbearing age and children, both critical target populations to prevent and mitigate ZIKV outbreaks ( 62 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Computational models have helped quantify the potential impact of and guide decision making for epidemics and outbreaks in the past, such as the 2009 H1N1 pandemic, [6][7][8][9][10][11][12][13][14][15][16] the ongoing Ebola outbreak that emerged in 2018, 17 and the 2015-2016 Zika outbreak. 18,19 Therefore, we developed a computational model to represent what may happen to each patient infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) and quantify potential resource use and direct medical costs (i.e., costs directly attributable to health care resource use for interventions and care that are specific to COVID-19 illness and would typically be paid out by third-party payers) in the U.S. under various conditions.…”
mentioning
confidence: 99%